Exercises to develop perception skills in grade V - Alzate, Betzaida B. 1935- (1977)
This study was an attempt to construct sample exercises to develop perception skills for Grade V pupils . This set may serve as a diagnostic test and/or sample materials for remediation. To determine the difficulty of each 18 reading selections which were based on and/or lifted from the UPSEC, ESS Guide V, the Dale-Chall Readability Formula was used. The Gates Reading Survey Form was used to determine the reading levels of 787 high school students. The study suggested that grouping should done according to the reading levels of the learners; that the students be trained to use perception skills in the acquisition of simple science concepts; that the development of reading skills be the result of the concerted effort of all teachers; and that science materials be within the reading levels of the learners.